2006
DOI: 10.1111/j.1600-0404.2005.00570.x
|View full text |Cite
|
Sign up to set email alerts
|

Centralized rehabilitation after severe traumatic brain injury - a population-based study

Abstract: Out of 117 patients in the prospective study, six died, and 92 (1.27 per 100,000 population per year) survived after a post-traumatic amnesia (PTA) period of at least 28 days. All 19 patients with PTA 7-27 days and 48% of survivors with PTA at least 4 weeks were discharged directly home. The incidence of patients vegetative at 1 month post-trauma was 0.29, and at 1 year 0.055 per 100,000 population. By comparison of 39 patients from the centralized unit injured in 2000-2003 with 21 patients injured in 1982, 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 14 publications
1
25
2
1
Order By: Relevance
“…This is in agreement with the recent study by Trivedi et al also using SIENA (Trivedi et al, 2007). While our patient population represented very severely injured survivors of TBI (Engberg et al, 2006), Trivedi studied a population of mixed injury severity ranging from mild to severe TBI. This probably explains why we found a greater decline in brain volume (mean −4.0%, median −2.9%) compared to their study (mean −1.43%).…”
Section: Global Volume Changessupporting
confidence: 79%
“…This is in agreement with the recent study by Trivedi et al also using SIENA (Trivedi et al, 2007). While our patient population represented very severely injured survivors of TBI (Engberg et al, 2006), Trivedi studied a population of mixed injury severity ranging from mild to severe TBI. This probably explains why we found a greater decline in brain volume (mean −4.0%, median −2.9%) compared to their study (mean −1.43%).…”
Section: Global Volume Changessupporting
confidence: 79%
“…According to recent research, rehabilitation after severe TBI should start in the acute phase of hospital care to optimize patients' outcomes and recovery potential (Khan et al, 2002). There have been several studies of early rehabilitation after severe TBI that support the benefit of early interventions (Engberg et al, 2006;Greenwood et al, 2004;Mackay et al,1992;Mammi et al, 2006;Sorbo et al, 2005). Mackay and associates (1992) concluded that ''aggressive rehabilitation during acute hospitalization'' contributed to a shorter total rehabilitation stay for the group that received acute rehabilitation.…”
mentioning
confidence: 99%
“…A Swedish study (Sorbo et al, 2005) concluded that an effective combination of medical and rehabilitation efforts resulted in shorter hospital stays and produced a good outcome/living situation for patients with severe brain damage (TBI or subarachnoid hemorrhage). A Danish study found that centralized rehabilitation after severe TBI resulted in better outcome compared to historical data from decentralized rehabilitation (Engberg et al, 2006). These studies were, however, limited by being either non-randomized controlled trials, or by their retrospective/cross-sectional design.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Com TCE (n = 17) ( ± ± ± ± DP) Sem TCE (n = 44) ( ± ± ± ± DP) Diabéticos (n = 27) ( ± ± ± ± DP) Não Diabéticos (n = 157) ( ± ± ± ± DP) Pré-Operatório (n=13) ( ± ± ± ± DP) Pós-Operatório (n=13) ( ± ± ± ± DP) (20,57,(100)(101)(102)(103)(104)(105)(106)(107) .…”
Section: Características Das Vítimas Avaliadas Com O Goatunclassified